The biological activity of serum bacterial lipopolysaccharides associates with disease activity and likelihood of achieving remission in patients with rheumatoid arthritis - J. Parantainen; G. Barreto; R. Koivuniemi; H. Kautiainen; D. Nordström; E. Moilanen; M. Hämäläinen; M. Leirisalo-Repo; K. Nurmi; K. K. Eklund (Arthritis Research & Therapy, 2022)
Abstract Background Dysbiotic intestinal and oral microbiota have been implicated in the pathogenesis of rheumatoid arthritis (RA), but the mechanisms how microbiota could impact disease activity have remained elusive. The aim of this study was to assess the association of the biological activity of serum lipopolysaccharides (LPS) with disease activity and likelihood of achieving remission in RA patients. Methods We measured Toll-like receptor (TLR) 4-stimulating activity of sera of 58 RA patients with a reporter cell line engineered to produce secreted alkaline phosphatase in response to TLR4 stimulation. Levels of LPS-binding protein, CD14, and CD163 were determined by ELISA assays. Results The patient serum-induced TLR4 activation (biological activity of LPS) was significantly associated with inflammatory parameters and body mass index at baseline and at 12 months and with disease activity (DAS28-CRP, p<0.001) at 12 months. Importantly, baseline LPS bioactivity correlated with disease activity (p=0.031) and, in 28 early RA patients, the likelihood of achieving remission at 12 months (p=0.009). The level of LPS bioactivity was similar at baseline and 12-month visits, suggesting that LPS bioactivity is an independent patient-related factor. Neutralization of LPS in serum by polymyxin B abrogated the TLR4 signaling, suggesting that LPS was the major contributor to TLR4 activation. Conclusion We describe a novel approach to study the biological activity of serum LPS and their impact in diseases. The results suggest that LPS contribute to the inflammatory burden and disease activity on patients with RA and that serum-induced TLR4 activation assays can serve as an independent prognostic factor. Graphical Abstract A graphical summary of the conclusions of the study.